Epidemiology and short-term outcomes of acute kidney injury among patients in the intensive care unit in Laos: a nationwide multicenter, prospective, and observational study - Sengthavisouk, Noot (BMC Med, 2020)
BACKGROUND: Acute kidney injury (AKI) has become a global health issue. Little is known about the disease burden in Laos. We aimed to evaluate the burden and outcomes of AKI as well as assess the availability of AKI treatment in Laos. METHODS: We performed a multicentric prospective observational study in adult patients who had been admitted to 5 intensive care units (ICU) in Laos. The data was serially collected on the first 28 days of ICU admission. Patients were diagnosed by the KDIGO 2012 criteria for AKI. We used AKI occurrence as the primary outcome and explored risk factors on the development and outcomes of AKI. RESULTS: We enrolled 1480 patients from 5 ICU centers across Laos from January to December 2016. After excluding patients with end-stage renal disease and those with incomplete data, AKI occurred in 508 of the 1460 enrolled patients (34.8%). Overall, the rates of maximum AKI staging were 4% for stage 1, 10.3% for stage 2, and 20.5% for stage 3. Risk factors for AKI were older age, obesity, cardiovascular diseases, respiratory diseases, renal diseases, oncologic diseases, and chronic kidney diseases. Only 1.8% of all participants received RRT. The mortality rate was 28.4% in non-AKI patients compared to 44.5% in AKI patients, which increased according to the stage of AKI (stage 1, 4.9%; stage 2, 28.3%; stage 3 66.8%; P < 0.001). There were 13.6% who were discharged against medical advice. CONCLUSIONS: AKI is a huge burden in Laos with under-recognition and poor outcomes.